RANCANG BANGUN ALAT PANJAT UNTUK PENDERES NIRA KELAPA DI KABUPATEN BANYUMAS - Achmad Zaki Yamani; Aswan Munang (Universitas Ahmad Dahlan Indonesia, 2019)
Coconut sugar is one of the leading commodities in Banyumas City, coconut sugar and it is derivative processing can make a high contribution to the development of the local economy of the community. This can be seen from the history of the production of coconut sugar whose trend is always increasing, in 2013 the production of coconut sugar was 206,026 tons / day, in 2014 it increased to 240 tons / day and in 2015 the production reached 250 tons / day. This study aims to find an area of improvement for the design of tree climbing aids that are in line with the expectations of the nira hikers in the Cilongok Banyumas City. In carrying out their work, the loudspeakers did not have much safety equipment, in a day, the loudspeakers had to climb 40 trees from morning to evening. The average height of each coconut tree that is climbed is around 20 until 30 meters. This study aims to design coconut climbing aids for the nira hardener with a quality function deployment (QFD) approach. In the process of retrieving data, the researcher identifies the desires of consumers, a questionnaire that has been determined and contains attributes in accordance with the quality plan that has been determined in the framework of the thought distributed to the subject. The way to find out the user anthropometry data is by measuring height, body dimensions, age, weight and length of work, so that we can obtain a reference for designing coconut tree climbing aids that are in accordance with the expectations of the palm fruit pusher.